Exploring the Hopes of Arabic Language Students Through the Scale to Assess Possible Selves (SAPS) in Metro City - Amrullah, M. Kholis; Zein, Umar Najih; Arifin, Ahmad; Wilailak, Wisetrat; Hadi Nurdi Hamzah (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
This study explores the motivational dimensions of Arabic language learning in Indonesia through the lens of the possible-selves theory, addressing a critical gap in research that has predominantly focused on English language learners. The main objective is to examine how students in Metro City envision their future selves in relation to Arabic language competence and to assess the applicability of the Scale to Assess Possible Selves (SAPS) in this context. Employing a quantitative approach, data were collected through questionnaires adapted from the SAPS instrument, translated into Indonesian for clarity, and analyzed using crosstab analysis with SPSS to identify relationships between learners’ self-perceptions, motivation, and institutional factors. The findings reveal significant and consistent gaps between students’ current abilities and their expected selves across multiple Arabic programs, suggesting a systemic aspiration, attainment mismatch influenced by program design and institutional support. The study’s novelty lies in its cross-institutional analysis that operationalizes the possible-selves framework within Arabic education, providing theoretical extension and practical implications for curriculum design, mentoring systems, and motivational interventions in Indonesian Islamic higher education. Future research is recommended to expand this framework through longitudinal and mixed-method approaches to examine the dynamic development of students’ possible selves across diverse Islamic higher education contexts